기후변화 대응을 위한 대구공항 공항시설 취약성 및 위험도 분석에 관한 연구 - 권달원; 김기웅; 안신영; Dal-One Kwon; Ki-Woong Kim; Shin-young Ahn (한국항공운항학회지, 2024)
Recently, the size and severity of disasters due to rapidly progressing global climate change are increasing, and situation prediction and response are also becoming difficult and complex. In addition, the proportion of public facilities among natural disaster damage related to climate change is increasing, and the importance of management of social infrastructure and public services is also increasing. Responses to climate change in the aviation sector are progressing in various aspects overall, but are showing somewhat different aspects. In other words, it appears that airlines are focusing on reducing aircraft engine emissions, which are the main cause of climate change, while airports are paying more attention to improving airport facilities and services as well as emissions. Considering these circumstances, this study aims to assess the vulnerability of airport facilities and analyze their risk to respond to climate change, focusing on airport facilities where airport operators play a leading role in responding to climate change in the aviation sector.